EFEKTIVITAS GAYA MENGAJAR COMMAND DENGAN SELF CHECK TERHADAP POLA TAKTIK PARALEL FUTSAL - Ganjar Cahya Ramadan; Iif Firmana (Journal of Physical Education and Sport Science, 2020)
This Research is based on the mistakes learning of attack strategy in Futsal, during matches or training. The Purpose of this research to know capability of students learn about attack strategy in Futsal, combined with two different teaching styles, that is command and self check. This research uses experimental by design pre-experimental with form intact-group comparison. The technique used is the test technique. The instrument used is Game Peformance Assessment Instrument (GPAI). The result from using teaching style command is (C=33,58) and then the result from using teaching style self check is (S= 29,33) results from the level of 0.05 and get the results of t count = 0.280, t table 1,795 or t count smaller than t table . Based on the results it can be concluded teaching style self check is more effective compared with teaching style self command to practice attack strategy futsal in extracurricular Junior High School 2 Kuningan.